Immigration & Ideas: What Did Russian Scientists 'Bring' to the US? - Ina Ganguli (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2014)
This paper examines how high-skilled immigrants contribute to knowledge diffusion using a rich dataset of Russian scientists and US citations to Soviet-era publications. Analysis of a panel of US cities and scientific fields shows that citations to Soviet-era work increased significantly with the arrival of immigrants. A difference-in-differences analysis with matched paper-pairs also shows that after Russian scientists moved to the US, citations to their Soviet-era papers increased relative to control papers. Both strategies reveal scientific field-specific effects. Ideas in high-impact papers and papers previously accessible to US scientists were the most likely to "spill over" to natives.
Keywords: J40; J61; O33; 330; high skill immigration; citations; innovation; Russia